The effects of a single dose of concentrated beetroot juice on performance in trained flatwater kayakers - Muggeridge, D. J.; Howe, C. C. F.; Spendiff, O.; Pedlar, C.; James, P. E.; Easton, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The aim of the current study was to determine the effects of dietary nitrate ingestion on parameters of sub- maximal and supramaximal exercise and time trial (TT) performance in trained kayakers. Eight male kayakers completed four exercise trials consisting of an initial discontinuous graded exercise test to exhaustion and three performance trials using a kayak ergometer. The performance trials were composed of 15 min of paddling at 60% of maximum work rate, five 10-s all-out sprints, and a 1 km TT. The second and third trials were preceded by ingestion of either 70 ml nitrate-rich concentrated beetroot juice (BR) or tomato juice (placebo [PLA]) 3 hr before exercise using a randomized crossover design. Plasma nitrate (PLA: 33.8 ± 1.9 µM, BR: 152 ± 3.5 µM) and nitrite (PLA: 519.8 ± 25.8, BR: 687.9 ± 20 nM) were higher following ingestion of BR compared with PLA (both p < .001). VO2 during steady-state exercise was lower in the BR trial than in the PLA trial (p = .010). There was no difference in either peak power in the sprints (p = .590) or TT performance between conditions (PLA: 277 ± 5 s, BR: 276 ± 5 s, p = .539). Despite a reduction in VO2, BR ingestion appears to have no effect on repeated supramaximal sprint or 1 km TT kayaking performance. A smaller elevation in plasma nitrite following a single dose of nitrate and the individual variability in this response may partly account for these findings.